2014
DOI: 10.1038/ncomms6493
|View full text |Cite
|
Sign up to set email alerts
|

Berberine activates thermogenesis in white and brown adipose tissue

Abstract: Obesity develops when energy intake exceeds energy expenditure. Promoting brown adipose tissue formation and function increases energy expenditure and hence may counteract obesity. Berberine (BBR) is a compound derived from the Chinese medicinal plant Coptis chinensis. Here we show that BBR increases energy expenditure, limits weight gain, improves cold tolerance and enhances brown adipose tissue (BAT) activity in obese db/db mice. BBR markedly induces the development of brown-like adipocytes in inguinal, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
274
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(292 citation statements)
references
References 69 publications
16
274
0
2
Order By: Relevance
“…Above studies indicate that a balance between WAT and BAT is necessary to maintain energy homeostasis and healthy body composition. Recent evidences have associated BAT with non-shivering thermogenesis, lipolysis, fatty acid oxidation, insulin sensitivity, and improved serum lipid profile (Zhang et al 2014). Study conducted by Gray et al showed that hyperinsulinemia precedes insulin resistance in mice lacking pancreatic leptin signaling (Gray et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Above studies indicate that a balance between WAT and BAT is necessary to maintain energy homeostasis and healthy body composition. Recent evidences have associated BAT with non-shivering thermogenesis, lipolysis, fatty acid oxidation, insulin sensitivity, and improved serum lipid profile (Zhang et al 2014). Study conducted by Gray et al showed that hyperinsulinemia precedes insulin resistance in mice lacking pancreatic leptin signaling (Gray et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, prolonged inhibition of adrenergic receptors decreases AMPK activity (25). Accordingly, the plant-derived alkaloid berberine or microRNA-455 enhances brown adipogenesis via activation of AMPK (26,27). In addition, AMPK stimulates glycolysis (28) and coupled respiration-mediated ATP generation in metabolic tissues (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…Thus pharmacological intervention that can reduce insulin hypersecretion and simultaneously alleviate insulin resistance is an attractive strategy to prevent beta-cell dysfunction due to their exhaustion. Berberine exerts hypoglycemic and hypolipidemic action via stimulating glucose uptake, reducing lipogenesis, and increasing energy expenditure in peripheral tissues [8,9,20]. Berberine can also decrease insulin levels in high-fat-fed rats [10].…”
Section: Discussionmentioning
confidence: 99%